مستوى تحقق كفايات التعليم الإلكتروني لأعضاء هيئة التدريس بكلية التربية بالدلم وقت جائحة كورونا - خير الله، منى عبداللطيف العوض; جعفر، سالي معاوية فتحي Jaafar, Sally Muawiah Fathi (المؤسسة العربية للتربية والعلوم والآداب, 2021)
هدفت الدراسة إلى معرفة درجة توافر كفايات التعليم الإلكتروني وممارستها لدي أعضاء هيئة التدريس بكلية التربية بالدلم جامعة الأمير سطام بن عبد العزيز بالخرج وقت جائحة كورونا. اتبعت الدراسة المنهج الوصفي التحليلي. طبقت الدراسة على عينة عشوائية تكونت من (65) عضو هيئة تدريس ومن في حكمهن. طبقت أدوات الدراسة من إعداد الباحثتان وجمع البيانات وتحليلها، توصلت الدراسة للنتائج الآتية: موافقة أعضاء هيئة التدريس بدرجة جيدة على تحقق اثنين من كفايات التعلم الإلكتروني، موافقة أعضاء هيئة التدريس بدرجة متوسطة على تحقق خمسة من كفايات التعلم الإلكتروني، موافقة أعضاء هيئة التدريس بشدة على الاستفادة من تسعة عبارات في تحقق كفايات التعلم الإلكتروني، موافقة أعضاء هيئة التدريس على ثلاثة فقرات في تحقق كفايات التعلم الإلكتروني في كلية التربية بالدلم وخلصت الدراسة على عدد من التوصيات الإيجابية للاستفادة منها في التعليم خاصة وقت الأزمات. The study aimed to find out the degree of availability and practice of e-learning competencies among the faculty members of the College of Education in Dalam, Prince Sattam bin Abdulaziz University in Al-Kharj, at the time of the Corona pandemic. The study followed the descriptive and analytical approach. The study was applied to a random sample of (65) faculty members and the like. The study tools prepared by the two researchers were applied, and the data collected and analyzed, the study reached the following results: The approval of the faculty with a good degree to achieve two e-learning competencies, the approval of the faculty members with a medium degree to achieve five e-learning competencies, the faculty strongly approve the use of nine phrases in the verification of e-learning competencies, the approval of the faculty members to three Paragraphs on the verification of e-learning competencies in the College of Education in Dalam. The study concluded on a number of positive recommendations to make use of them in education, especially in times of crisis.
Keywords: الكفايات التدريسية -- تكنولوجيا التعليم -- جائحة كورونا "كوفيد-19" -- أعضاء هيئة التدريس -- السعودية